A rare cause of susceptibility to neutropenic sepsis in a patient with metastatic pancreas cancer. (3rd April 2014) - Suarez Martinez-Falero, Beatriz; Gillmore, Roopinder
Abstract : A 71-year-old patient receiving combination chemotherapy (irinotecan, oxaliplatin and 5-fluorouracil (5-FU)) for metastatic pancreas cancer was admitted after her first cycle of chemotherapy with a severe and unexpectedly prolonged episode of neutropenic sepsis associated with pancytopenia and marked mucositis. Owing to the unusual picture, the patient was tested for mutations in the gene encoding the enzyme dihydropyrimidine dehydrogenase (DPD)—an enzyme involved in the metabolism of the chemotherapy drug 5-FU. The patient was found to be heterozygous for a mutation, DPD IVS14+1G>A, leading to the severe toxicity exhibited following this regimen caused by delayed metabolism of 5-FU. She was treated aggressively with supportive care and recovered from this episode. Importantly she was subsequently switched to an alternative chemotherapy regimen to treat her disease. She continues to maintain an excellent quality of life some 9 months after her initial diagnosis on third-line chemotherapy.